A Comparison of Explicit and Implicit Approaches to EAP Teaching to Postgraduate Students - O. A. Boginskaya (Высшее образование в России)
The present study aims to explore the role of explicit and implicit approaches in developing pragmatic competence in postgraduate students as part of the Foreign Language course. 32 students were divided into two groups depending on the type of teaching approach for six weeks of instruction. Research proposals written by each group after the interventions were examined with the aim of comparing the employment of pragmatic features such as stance-taking resources and their frequencies. In order to investigate the effects of stance-taking instruction, this study adopted a combination of quantitative and interpretative analysis methods. The results revealed significant differences in the use of stance resources by the postgraduate students exposed to explicit vs implicit instruction. In terms of compliance with the academic writing norms, the explicit instruction was found to be more effective than the implicit one. The analysis found that while the explicit group tended to mitigate their claims and hide authorial presence, the students exposed to the implicit instruction expressed stronger commitments to propositional content and showed writer visibility in the text, which considers to be inappropriate in English-language academic writing. The findings point to important considerations for EAP teaching and future research into academic discourse and contribute to previous studies of the benefits of instruction in the development of pragmatic competence. The results may be employed by curriculum designers to create materials for L2 writers and EAP instructors in their teaching practice.